Lipoamide dehydrogenase is essential for both bloodstream and procyclic Trypanosoma brucei - Roldán Sánchez, Angela Maria; Comini, Marcelo A.; Crispo, Martina; Krauth-Siegel, Renate (Molecular microbiology, 2011)
Lipoamide dehydrogenase (LipDH) is a component of four mitochondrial multienzyme complexes. RNA interference or the deletion of both alleles in bloodstream Trypanosoma brucei resulted in an absolute requirement for exogenous thymidine. In the absence of thymidine, lipdh−/− parasites showed a severely altered morphology and cell cycle distribution. Most probably, in bloodstream cells with their only rudimentary mitochondrion, LipDH is required as component of the glycine cleavage complex which generates methylene-tetrahydrofolate for dTMP and thus DNA synthesis. The essential role of LipDH in bloodstream parasites was confirmed by an in vivo model. Lipdh−/− cells were unable to infect mice. Our data further revealed that degradation of branched-chain amino acids takes place but is dispensable. In cultured bloodstream - but not procyclic - African trypanosomes, the total cellular concentration of LipDH increases with increasing cell densities. In procyclic parasites, LipDH mRNA depletion caused an even stronger proliferation defect that was not reversed by thymidine suggesting that in the fully elaborated mitochondrion of these cells the primary effect is not on the glycine cleavage complex. Since the medium used for the cultivation of procyclic cells was not supplemented with glucose, impairment of the 2-ketoglutarate dehydrogenase complex is probably the main effect of LipDH depletion.